2017
DOI: 10.1016/j.bjm.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of Streptococcus agalactiae isolated from mastitis in Brazilian dairy herds

Abstract: Streptococcus agalactiae is one of the most common pathogens leading to mastitis in dairy herds worldwide; consequently, the pathogen causes major economic losses for affected farmers. In this study, multilocus sequence typing (MLST), genotypic capsular typing by multiplex polymerase chain reaction (PCR), and virulence gene detection were performed to address the molecular epidemiology of 59 bovine (mastitis) S. agalactiae isolates from 36 dairy farms located in the largest milk-producing mesoregions in Brazil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
67
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 54 publications
10
67
1
1
Order By: Relevance
“…We demonstrated that the bac gene was absent in the four human GBS isolates. Similar results were observed for GBS isolates causing mastitis in Brazilian dairy herds, irrespective of their serotypes (Ib, Ia or II) (Carvalho‐Castro et al ). Given the small sample sizes involved, the fact that only GBS strains of serotypes Ib, Ia and II were detected in both populations may have been a coincidence.…”
Section: Discussionsupporting
confidence: 80%
“…We demonstrated that the bac gene was absent in the four human GBS isolates. Similar results were observed for GBS isolates causing mastitis in Brazilian dairy herds, irrespective of their serotypes (Ib, Ia or II) (Carvalho‐Castro et al ). Given the small sample sizes involved, the fact that only GBS strains of serotypes Ib, Ia and II were detected in both populations may have been a coincidence.…”
Section: Discussionsupporting
confidence: 80%
“…; Carvalho‐Castro et al . ). Although they are available in a very short time in the environment, S. agalactiae survives inside the mammary gland for a long time (Kefee ).…”
Section: Introductionmentioning
confidence: 97%
“…Genetic diversity and clonal relatedness of S. agalactiae strains recovered from human and animal infections have been previously demonstrated by pulsed-field gel electrophoresis (PFGE) (Pinto et al 2013). Studies performed in different countries showed capsular types Ia, II, III, IV and V predominant in human and bovine infections, including Brazil (Pinto et al 2013;Carvalho-Castro et al 2017;Pang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In GBS, capsular serotyping either with antibodies or by ‘molecular serotyping’ (sequencing of the capsular operon) has become a widely used method of typing for population studies (1720) and, currently, S . agalactiae can be divided into ten capsular serotypes (Ia, Ib and II-IX) (18, 21). Determining capsular serotypes is also critical for vaccine formulation since CPS is highly immunogenic and can confer excellent protection against infections by the homologous CPS serotype (20, 22, 23).…”
Section: Introductionmentioning
confidence: 99%